Organizational Citizenship Behavior as a Mediator of the Effect of Organizational Commitment and Job Satisfaction on Performance - Kartika Putra, Bayu Samudra; Suswanti, Endang; Mu’awanah, Umi (International Journal Labs, 2024)
This study aims to test and analyze the effects of: 1) organizational commitment to organizational citizenship behavior, 2) job satisfaction to organizational citizenship behavior, 3) organizational commitment to performance, 4) job satisfaction affects performance, 5) organizational citizenship behavior to performance, 6) organizational commitment to performance through organizational citizenship behavior, 7) job satisfaction to performance through organizational citizenship behavior. This research was conducted at PT. Waskita Karya Jakarta Building Division in April-June 2024, carried out at PT. Waskita Karya (Perseo) Building Division in May-June 2024. The population is 456 employees, then sampled with the Slovin formula and with proportional random sampling of each department a sample of 213 employees was obtained. Primary data related to the research variables were obtained by questionnaires given via google form. Once the data is collected, it is analyzed with Smart Partial Lease Square (SPLS). However, previously a validity and reliability test was carried out. The hypothesis was tested by a t-test with a 5% alpa. The results prove that: 1) organizational commitment has an effect on organizational behavior citizenship. 2) job satisfaction affects organizational behavior citizenship, 3) organizational commitment affects employee performance. 4) Job satisfaction affects performance, 5) Organizational behavior citizenship affects employee performance. 6) Organizational citizenship behavior is able to increase/mediate the influence of organizational commitment on employee performance. 7) Organizational citizenship behavior is able to increase/mediate the influence of job satisfaction on employee performance.